Changes In Mathematics Teachers' Questioning Techniques Through The Lesson Study Process - Ong, Ewe Goh (2010)

(untitled)
This study aimed to examine the changes in the mathematics teachers' questioning techniques through lesson study process. Two main research objectives were: i) to examine the changes in the mathematics teachers' questioning techniques in terms of probing, guiding and factual questioning when teaching mathematics; ii) to investigate the differences in the changes in questioning techniques among novice and experienced mathematics teachers. This study was conducted in Sarawak whereby ten (experienced and novice) teachers from two schools, namely School M (primary) and School P(secondary) underwent the lesson study process for fifteen months. Kajian ini bertujuan mengkaji perubahan teknik penyoalan guru matematik melalui proses lesson study. Dua objektif utama kajian ini ialah; i) menyiasat perubahan teknik penyoalan guru matematik dari segi mencungkil, membimbing dan penyoalan fakta; ii) mengkaji perbezaan perubahan teknik penyoalan dalam kalangan guru baharu dan guru berpengalaman. Kajian ini dilaksanakan di Sarawak, di mana sepuluh orang guru matematik (berpengalaman dan baharu) dari dua buah sekolah, Sekolah M (sekolah rendah) dan Sekolah P (sekolah menengah) telah melalui proses lesson study selama lima belas bulan.